Quality Oriented Management - Mohammad Habibi (International Journal of Management and Business Intelligence, 2023)
Quality management is a phenomenon. Advanced culture that supports arts and crafts allows shoppers to choose goods with higher quality standards compared to the normal stuff. In a society that appreciates the arts and crafts, one of the tasks of the management company or owner of the company is the head of the workshop, as well as train and supervise employees and interns. The company sets the standard, assesses the work of the employees and orders rework or repair is necessary. Jobs in crafts have a limitation that is only capable of producing little other products, but has the advantage that each product can be made independently in accordance with the wishes of the customer. Craft work approach towards quality score is the primary input when the initial establishment of quality management as a part of management science.